Review of the scientific journal Compendium (issn: 2477-9725) of the Universidad Centroccidental Lisandro Alvarado (Revista Electrónica REDINE, 2021)
This review describes the process of creation and consolidation of the scientific journal COMPENDIUM (ISSN: 2477-9725) of the Universidad Centroccidental Lisandro Alvarado, Venezuela, attached to the Dean of Economic and Business Sciences. Publication begins in 1995, with biannual periodicity, open access and free; It is currently indexed in Scielo Venezuela, Dialnet, Redib, DOAJ, Latindex Catalog, Redalyc and Clase. It contributes to the dissemination of scientific works in Social Sciences by national and international researchers, on issues of administration, accounting, law, economics, quantitative techniques, methodology and epistemology, environment, history, political science and sociology.
Keywords: scientific journal; social science; UCLA; university; Venezuela